Revisiting virtual difference ideals - Chatzidakis, Z; Hrushovski, E (2016)
The main idea of [4] was that structures built from periodic prime ideals have better properties from the usual ones built from invariant ideals; but unable to work with periodic ideals alone, we had to generalise further to a somewhat ephemeral setting called virtual ideals. This text has two purposes. It corrects an error in [4] discovered by Tom Scanlon's UCB seminar, recovering all results for all virtual ideals. In addition, based on results in [3], we describe a wide family of difference equations where virtual ideals reduce to periodic ideals.